Analysis of Factors Affecting Audit Report Lag on Service Companies Listed on The Indonesia Stock Exchange (IDX) For The 2017-2020 Period - Wenny Anggeresia Ginting; Abtri Nadya Margaretha P; Ayu Farida Sianturi (Kusuma Negara Business School, 2022)
Financial statements are a reference for companies and investors in making decisions. The function of financial reports which is always used as a benchmark in making decisions by various interested parties makes financial statements required to always be presented accurately. In addition, timeliness in the presentation of financial statements is also very necessary. The more timely the financial statements are presented, the faster the decision making will be made so that the decisions taken will be considered more accurate and precise and useful for the company. In this research, we analyze the factors that affect the Audit Report Lag in service companies listed on the Indonesia Stock Exchange. This study uses the independent variables, namely firm age, profitability, solvency and firm size. The data we obtained was processed using the SPSS data processing application. The tests used in this study are the classical assumption test, the coefficient of determination test, the t test and the F test. The results of this study indicate that of the four independent variables used in this study, only the profitability variable affects the audit report lag simultaneously and partially, while the other three variables, namely firm size, firm age and profitability have no effect on the dependent variable audit hassle lag.